Four priorities for Zambia after the 2021 elections - Resnick, Danielle (The Conversation, 2021)
Whoever wins Zambia’s 2021 general elections will face two key challenges: reviving the country’s democratic credentials and stimulating the economy. To achieve this, the new administration must have at least four priorities. These are regaining credibility with the international financiers, fighting corruption, curtailing the dominance of the executive branch of government, and ending the reign of terror by political party vigilantes, known as “cadres”.